2013
DOI: 10.1016/j.chroma.2012.12.044
|View full text |Cite
|
Sign up to set email alerts
|

An improved approach to hydrophilic interaction chromatography of peptides: Salt gradients in the presence of high isocratic acetonitrile concentrations

Abstract: Hydrophilic interaction chromatography (HILIC) for separations of peptides has been employed infrequently, particularly considering that this technique was introduced over 20 years ago. The present manuscript describes a radical departure from the traditional HILIC elution approach, where separations are achieved via increasing salt (sodium perchlorate) gradients in the presence of high isocratic concentrations (>80%) of acetonitrile, denoted HILIC/SALT. This initial study compared to reversed-phase chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Similar to that observed in HILIC/CEX, the HILIC/SALT approach can also provide good separations of closely related peptides, as well as amphipathic, α‐helical peptides, with substitution in the hydrophilic part . Last but not least, peak shapes were generally improved in HILIC/CEX and HILIC/SALT compared to HILIC . However, these techniques are obviously less MS friendly than pure HILIC due to the presence of nonvolatile additives such as NaClO 4 .…”
Section: Applications Of Hilic To Peptidesmentioning
confidence: 55%
See 2 more Smart Citations
“…Similar to that observed in HILIC/CEX, the HILIC/SALT approach can also provide good separations of closely related peptides, as well as amphipathic, α‐helical peptides, with substitution in the hydrophilic part . Last but not least, peak shapes were generally improved in HILIC/CEX and HILIC/SALT compared to HILIC . However, these techniques are obviously less MS friendly than pure HILIC due to the presence of nonvolatile additives such as NaClO 4 .…”
Section: Applications Of Hilic To Peptidesmentioning
confidence: 55%
“…A linear increasing salt gradient is applied to elute peptides by an increase in the mobile phase polarity via the presence of salt . Similar to that observed in HILIC/CEX, the HILIC/SALT approach can also provide good separations of closely related peptides, as well as amphipathic, α‐helical peptides, with substitution in the hydrophilic part . Last but not least, peak shapes were generally improved in HILIC/CEX and HILIC/SALT compared to HILIC .…”
Section: Applications Of Hilic To Peptidesmentioning
confidence: 79%
See 1 more Smart Citation
“…Contaminated waters may cause delays in the molting cycles with adverse outcome on reproduction of these organisms. These results show that the multiplexed SRM protein quantification could be a pertinent method to complement the data obtained from the physiological measures used in the analysis (molt stage, oocyte size) [26]. …”
Section: Biological Validationmentioning
confidence: 95%
“…Moreover, charged groups in bonded functionalities could provide the possibility of ion-exchange with oppositely charged solutes while improving hydrophilicity, and thus a HILIC/ion-change mixedmode chromatographic system is obtained. It was reported that HILIC/ion-exchange showed many advantages (such as tunable selectivity, more efficient retention and better separation) for the application of peptides [7], small molecular drugs [8], and proteins [9]. Recently some new HILIC stationary phases were developed and exhibited HILIC/ion-change mixed-mode retention behavior.…”
Section: Introductionmentioning
confidence: 99%